A review of the genetic mechanisms generating igneous charnockite: CO2 flushing and crystal-melt segregation in mushy reservoirs - Zhao, Kai; Xu, Xisheng; Klemd, Reiner; He, Zhenyu; Zhang, Xisong (Earth-Science Reviews, 2023)
Igneous charnockites are high-temperature orthopyroxene-bearing granitoids, which constitute an important part of many high-grade terranes. High temperature (typically >750–800 °C) is considered to be a key factor regarding the formation of igneous charnockites, because orthopyroxene reacts with hydrous melts to form biotite and/or amphibole at low temperatures as predicted by equilibrium phase relations. Microstructural records of igneous charnockites suggest that the hydrous crystallization reaction occurs at near equilibrium conditions. Thus, it remains a puzzling question how orthopyroxene is preserved in granitoids that generally solidify at H2O-saturated solidus temperatures (<700 °C). Here, we synthesize mineralogical, petrological, and geochemical data for 32 charnockite plutons worldwide to evaluate the possible preservation mechanisms of orthopyroxene in granitoids. These igneous charnockites are classified as I-A-S types based on their mineral assemblages and whole-rock compositions. The orthopyroxene crystals in the igneous charnockites systematically have lower Al2O3 contents than those in metamorphic rocks, suggesting a magmatic origin of the former. Magmatic orthopyroxene is possibly preserved by two mechanisms, preventing back-reactions with hydrous melts: one mechanism deduced from fluid-inclusion studies highlights the importance of CO2, which can reduce the H2O activity and elevate the solidus temperature to the stability field of orthopyroxene. Physical constraints on fluid transport suggest that this mechanism is feasible when an orthopyroxene-bearing mushy reservoir is flushed by large amounts (>10–20 vol%) of CO2-rich fluids, which could form a permeable flow through bubble channels in the pore medium and significantly elevate the CO2 content (>1000 ppm at pressures of >0.2 GPa) dissolved in the interstitial melts. Available fluid-inclusion studies suggest that such a mechanism may have played an important role in the formation of some I- and A-type charnockites. Nonetheless, deducing the fluid composition solely from fluid-inclusion studies is ambiguous, since the trapping of fluid inclusions may leave a potentially non-representative record due to the different wetting characteristics of CO2 and H2O, as well as post-trapping grain-boundary migration recrystallisation, favoring the entrapment of CO2-rich inclusions. A further alternative mechanism is to extract hydrous melts from an orthopyroxene-bearing mush, thereby restricting the back-reaction of orthopyroxene during progressive crystallization. Igneous charnockites have maximum P2O5 contents of up to 1.0–1.2 wt% at 55–60 wt% SiO2 and Zr contents of up to >400–600 ppm at 60–65 wt% SiO2. The nonsynchronous variations in P2O5 and Zr contents can best be explained by melt extraction from a mush that saturates apatite earlier than zircon during magma evolution. This process produces apatite- and zircon-rich cumulate charnockites that have significantly higher P2O5 and Zr contents than global orthopyroxene-free granitoids. Many I-A-S type charnockites are believed to have formed through this mechanism and represent cumulate granitoids that had lost a significant amount (>20–40%) of hydrous interstitial melt. Our study reveals that the formation of igneous charnockite depends on extreme magmatic processes such as flushing of large amounts of CO2 or high degree of crystal-melt segregation, and not merely on the high temperature of crystallization. Further studies on igneous charnockite should shed new light on quantifying the carbon flux and understanding the differentiation of the continental crust.
CRIS-Team Scopus Importer:2023-01-20
Keywords: CO; Crystal mush; Crystal-liquid segregation; Igneous charnockite; Orthopyroxene